Ruptured cerebral mycotic aneurysm, an unusual infective endocarditis presentation. - Tiago Alves; Rita Ivo; Marta Rebelo; Eduarda Carmo (Galicia Clínica, 2020)
Although septic embolization associated with infective endocarditis is relatively frequent, mycotic cerebral aneurysms are a rare and potentially fatal complication. The authors report the case of a woman admitted with a cerebral haemorrhage due to mycotic aneurysm rupture, which led to a subacute infective endocarditis diagnosis. The patient underwent craniotomy with aneurysm excision and mitral valvuloplasty due to severe valvular insufficiency, with a favorable clinical outcome. The authors make a brief review, highlighting the challenge of the management of these patients, especially at surgical approach, which requires an individualized therapy strategy based on patient evolution.